The first report of pregnancies following blastocyst automated vitrification in Europe - Dal Canto, Mariabeatrice; Moutier, Clarissa; Brambillasca, Fausta; Guglielmo, Maria Cristina; Bartolacci, Alessandro; Fadini, Rubens; Renzini, Mario Mignini; Buratini, Jose [UNESP] (Elsevier B.V., 2019)
Embryo cryopreservation is a valuable technique in assisted reproductive technology (ART) that increases cumulative pregnancy rates and allows postponement of embryo transfer in patients with undesirable uterine or clinical conditions. Although vitrification has been considered the most efficient method to freeze oocytes and embryos, it is time-consuming and highly operator-dependent. Gavi (R) is the first semi-automated machine for vitrification capable of controlling crucial variables such as temperature, volume, concentration and exposure time during the vitrification process. We report the first two pregnancies obtained with blastocysts cryopreserved with the Gavi (R) semi-automated vitrification system in Europe. These outcomes suggest that the utilization of semi-automated vitrification may contribute to improve the outcomes and laboratory logistics of fertility clinics. (C) 2019 Elsevier Masson SAS. All rights reserved.
Keywords: Cryopreservation; Automated vitrification; Gavi (R); Pregnancy; Blastocyst